Transfromation of Traditional Marketing Strategy to Digital ; Challenges and Opportunities for Retailers - Petrus Loo (PT. Hafasy Dwi Nawasena, 2025)
The transformation of marketing from traditional to digital methods presents both challenges and opportunities for retailers. Traditional marketing, such as print and television advertising, is increasingly losing its effectiveness in targeting specific audiences, while digital marketing offers flexibility and advanced analytics tools. This study analyzes retailers' shifting marketing strategies using a descriptive-exploratory qualitative approach, with interviews with 25 participants, consisting of business owners and digital marketing experts. The results showed that limited digital skills and financial constraints are the main barriers for SMEs in adopting digital marketing. Competition with big brands that are more experienced in data-driven marketing is also a challenge. However, low-cost strategies such as SEO and organic marketing on social media can be effective alternatives. In addition, data-driven personalization increases customer engagement, while omnichannel strategies enable the integration of online and offline shopping experiences. Technological innovations, such as influencer-based marketing, live shopping, and augmented reality (AR), further enhance the customer shopping experience. Retailers that successfully adopt big data and artificial intelligence (AI) have a competitive advantage in understanding customer preferences more accurately. Therefore, the combination of data analytics, omnichannel strategy, and technological innovation is the key to modern digital marketing success.